Highly active antiretroviral therapy adherence and its determinants in selected regions in Indonesia (Faculty of Medicine Universitas Indonesia, 2011)
Background: Highly active antiretroviral therapy (HAART) can reduce morbidity and mortality of HIV-infected patients. However, it depends upon adherence to medication. The objective of this study was to examine the adherence to HAART and to evaluate individual patient characteristics i.e. self-efficacy, depression level, and social support and to finally determine HAART adherence in selected regions in Indonesia. Methods: This cross-sectional study was conducted in Jakarta, Malang, Bandung, Makasar and Banda Aceh. The subject of the study was HIV-infected patients who were older than 13 years old and had taken HAART for at least a month. They were recruited consecutively then asked how many pills they had missed during the previous month. Poor adherence can be stated if the percentage of adherence rate is below 95%. HIV treatment adherence self-efficacy scale (HIVASES), Beck Depression Inventory (BDI-II) and Interpersonal Support Evaluation List (ISEL) was adapted to assess self-efficacy, depression level and social support, respectively. Results: We found that 96% (n=53) of the subjects adhered to HAART. There were no associations between adherence with self-efficacy, depression level, and social support. The main cause of non-adherence in this study was 'simply forget’. Conclusion: Adherence to HAART was found to be high and not associated with self-efficacy, depression level and social support in some central regions in Indonesia. (Med J Indones 2011; 20:50-5) Keywords: adherence, depression, HAART, HIV, self-efficacy, social support